Dragonflies (Odonata) of Bachok Coast, Kelantan and Promoting Common Names. - Y., Norma-Rashid (Malaysian Journal of Science, 2010)
A brief study of odonates in the coastal area of Bachok, Kelantan found 16 species, belonging to two families Coenagrionidae (made up 25 % of the population) and Libellulidae (75 %). The common names used here are accepted internationally for cosmopolitan species, while others are coined to reflect local descriptions. The Eastern Scarlet, Crocothemis servilia (Drury, 1770) was most predominant followed by the Pinhead Midget, Agriocnemis femina (Brauer, 1868) while the rest of the species occurred in moderate numbers. Population numbers were biased towards males rather than females which was reflective of male tendency to exploit water as a reproductive strategy in acquiring mates.